The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11191-022-00323-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Trust in Scientists to Explain Health-Related Behaviors in Response to the COVID-19 Pandemic

Abstract: The devastating COVID-19 pandemic has cast a light on the question of why trust in scientists is important. This mixed-method study aimed to explore the study participants’ trust in scientists about getting the COVID-19 vaccine. It also aimed to reveal which key sources of information participants followed about the pandemic. Participants’ health-related behaviors and justifications for their behaviors as a response to the pandemic were also explored to understand how trust in scientists and sources of informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…In this study, the vast majority of respondents reported trusting information about the viruses from scientific experts. This result coupled with findings from recent studies on the role of scientific experts, physicians, and scientific journals highlights the significance of reliable sources of information in providing accurate knowledge, with a possible positive impact on health behavior [ 44 , 49 , 85 ].…”
Section: Discussionmentioning
confidence: 72%
“…In this study, the vast majority of respondents reported trusting information about the viruses from scientific experts. This result coupled with findings from recent studies on the role of scientific experts, physicians, and scientific journals highlights the significance of reliable sources of information in providing accurate knowledge, with a possible positive impact on health behavior [ 44 , 49 , 85 ].…”
Section: Discussionmentioning
confidence: 72%
“…The most commonly referenced behavioral effects pertain to health behaviors in response to false claims (e.g., antivaccine movements, speculated vaccine-autism link, genetically modified mosquitos and the Zika virus, COVID-19; Bode & Vraga, 2017; Bronstein et al, 2021; Galanis et al, 2021; Gangarosa et al, 1998; Greene & Murphy, 2021; Joslyn et al, 2021; Kadenko et al, 2021; Loomba et al, 2021; Muğaloğlu et al, 2022; van der Linden et al, 2020; Van Prooijen et al, 2021; Xiao & Wong, 2020). The same association has also been made between misinformation associated with anthropogenic climate change and resistance to adopting proenvironmental behaviors (Gimpel et al, 2020; Soutter et al, 2020).…”
Section: The “Problem” Of Misinformationmentioning
confidence: 99%
“…Оба они выступают как частные варианты более широкого комплекса установок и идей, отражающих склонность ставить под сомнение достижения и постулаты современной науки, который включает в себя такие явления, как отрицание климатических изменений или теории эволюции и неприятие ГМО [Gemenis, 2021;Rutjens et al, 2021;Scheitle, Corcoran, 2021;Reinemann et al, 2022;Priniski, Holyoak, 2022]. Характерно, что люди, демонстрирующие высокий уровень доверия науке, в большей степени соблюдают рекомендованные ВОЗ и национальными правительствами меры по предотвращению заражения коронавирусом [Muğaloğlu et al, 2022].…”
Section: обзор литературыunclassified